Tussilagone Inhibits Osteoclastogenesis and Periprosthetic Osteolysis by Suppressing the NF-κB and P38 MAPK Signaling Pathways - Hu, Xuantao; Yin, Ziqing; Chen, Xia; Jiang, Guangyao; Yang, Daishui; Cao, Ziqin; Li, Shuai; Liu, Zicheng; Peng, Dan; Dou, Pengcheng (Frontiers in Pharmacology, 2020)
Background Aseptic prosthetic loosening is one of the main factors causing poor prognosis of limb function after joint replacement and requires troublesome revisional surgery. It is featured by wear particle-induced periprosthetic osteolysis mediated by excessive osteoclasts activated in inflammatory cell context. Some natural compounds show antiosteoclast traits with high cost-efficiency and few side effects. Tussilagone (TUS), which is the main functional extract from Tussilago farfara generally used for relieving cough, asthma, and eliminating phlegm in traditional medicine has been proven to appease several RAW264.7-mediated inflammatory diseases via suppressing osteoclast-related signaling cascades. However, whether and how TUS can improve aseptic prosthetic loosening via modulating osteoclast-mediated bone resorption still needs to be answered. Methods We established a murine calvarial osteolysis model to detect the preventative effect of TUS on osteolysis in vivo. Micro-CT scanning and histomorphometric analysis were used to determine the variation of bone resorption and osteoclastogenesis. The anti–osteoclast-differentiation and anti–bone-resorption bioactivities of TUS in vitro were investigated using bone slice resorption pit evaluation, and interference caused by cytotoxicity of TUS was excluded according to the CCK-8 assay results. Quantitative polymerase chain reaction (qPCR) analysis was applied to prove the decreased expression of osteoclast-specific genes after TUS treatment. The inhibitory effect of TUS on NF-κB and p38 MAPK signaling pathways was testified by Western blot and NF-κB-linked luciferase reporter gene assay. Results TUS better protected bones against osteolysis in murine calvarial osteolysis model with reduced osteoclasts than those in the control group. In vitro studies also showed that TUS exerted antiosteoclastogenesis and anti–bone-resorption effects in both bone marrow macrophages (BMMs) and RAW264.7 cells, as evidenced by the decline of osteoclast-specific genes according to qPCR. Western blotting revealed that TUS treatment inhibited IκBα degradation and p38 phosphorylation. Conclusions Collectively, our studies proved for the first time that TUS inhibits osteoclastogenesis by suppressing the NF-κB and p38 MAPK signaling pathways, therefore serving as a potential natural compound to treat periprosthetic osteolysis-induced aseptic prosthetic loosening.